Ancient angels : conceptualizing angeloi in the Roman Empire - Cline, Rangar. (Religions in the Graeco-Roman World, 2011)
Although angels are typically associated with Judaism, Christianity, and Islam, Ancient Angels demonstrates that angels (angeloi) were also a prominent feature of non-Abrahamic religions in the Roman era. Following an interdisciplinary approach, the study uses literary, inscriptional, and archaeological evidence to examine Roman conceptions of angels, how residents of the empire venerated angels, and how Christian authorities responded to this potentially heterodox aspect of Roman religion. The book brings together the evidence for popular beliefs about angels in Roman religion, demonstrating the widespread nature of speculation about, and veneration of, angels in the Roman Empire